NILAI TUKAR NELAYAN DAN KONTRIBUSINYA DALAM PEMENUHAN KEBUTUHAN RUMAH TANGGA NELAYAN DI KABUPATEN TANJUNG JABUNG BARAT - Asmaida Asmaida (Universitas Batanghari Jambi, 2013)
Fisheries sub-sector is one of the potential of marine resources and fisheries that have contributed significantly to the Indonesian economy . West Tanjung Jabung area has the potential of fishing is big enough that extends from West Tanjung Jabung border to the border with the province of Riau , with the potential for marine waters in 2010 reached 21,497.7 tons . The purpose of this study was to determine : 1 ) . Magnitude of fishermen household income , 2 ) . Magnitude of the contribution of fishing effort in meeting the needs of fishermen households , 3 ) . Magnitude Exchange Fishermen ( NTN ) , and 4 ) . Fishermen welfare level . The sampling technique used was a randomized ( random sampling ) with a total sample of 245 households of fishermen or of ± 26 % of total revenues of venture populasiUntuk analyze fisheries used the formula : TR = Q x P , analyzing profit : π = TR - TC , analyze revenue contribution : Kp = Pp / Prt x 100 % , then to analyze the exchange rate Fishermen : NTN = Yt / Et and analyze Fishermen Exchange Index : INTN = ( IYT / IET ) x 100 % .The results showed that , the average amount per month of income to fishing in West Tanjung Jabung Rp.6.007.385 , 00 , gross income from non-operating fishing Rp.122.816 , 33 . Total household income of fishermen Rp.6.130.201 , 33 . Contribution to fishing on total household income of fishermen in West Tanjung Jabung amounting Rp.6.007.385 , 00 or 98.00 % , the remaining Rp . 122,816.33 or 2.00 % comes from non to fishing. Exchange fishermen in West Tanjung Jabung during the period August-September 2013, the total household income of fishermen is at 1.72 and the exchange rate of the income of fishermen to fishing at 2.34 , indicating that households are concerned fishermen have welfare level sufficient to meet the primary needs of life and has the potential to consume non primary needs or to save money, either from the family or of the total revenue receipts to fishing.Keywords: NTN, INTN, Contribution